Environmental Ethics in Islāmic Perspective: Relevance and Application (Philosophy and Progress, 2024)
God has created all living and non-living things with a distinctive purpose. As the Sustainer of all, He has also arranged for each living organism a desirable environment that provides sustainable items. So, each life requires a sound environment for sustainability. Ecological studies help us understand organisms’ relationship to the environment around them. As God’s highest creation, humans have a close relationship with Nature to maintain and sustain their lives in vibrant caravans. The philosophical interpretations do accept the intimate relationship between humanity and Nature. However, our lifestyle is based on the rich consumption of resources, the development of new technologies and sciences for processing natural resources, burning fossil fuels, and discharging harmful radiation, which has alienated Nature from humanity. We can also point out other causes responsible for a radical break between human society and Nature. The Qur’ān and the Sunnah of the Prophet of Islām are the primary sources of all arts and thoughts. They may lead us to develop an Islāmic perspective on ecological crises and help us solve them. It is attempted here to understand some of the vital environmental phenomena in the light of these sources of Islām. There is intrinsic goodness, beauty, harmony and orderliness in the creation of God; everything in it, the sky and earth, including the sun, moon, stars, water, air, land and a thousand other things have been created for the benefit of man. The Creator created the universe with a Divine trust, which he had accepted and blessed to live in. He thanks God for all bestowed gifts practical in his entire gamut of human emotional life. From the Islāmic perspective, environmental ethics has become intrinsically relevant to dealing with all issues related to ecological crises. In the present paper, we are attempting to briefly discuss the Islāmic perspective on environmental ethics with particular reference to the Qur’ān and the traditions of Prophet Muhammad. It is assumed that the Islāmic framework on the said topic can also pave the way to bring out its relevance and application in crucial times.Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 1-20